2015
DOI: 10.1016/j.pharep.2014.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress as an etiological factor and a potential treatment target of psychiatric disorders. Part 1. Chemical aspects and biological sources of oxidative stress in the brain

Abstract: Oxidative stress is a dysfunctional state of living cells, caused by the disturbance of the pro-/antioxidative equilibrium. This dynamic equilibrium, constitutive for all aerobic organisms, is an inevitable necessity of maintaining the level of oxidative factors on non-destructive value to the cell. Among these factors reactive oxygen species (ROS) and reactive nitrogen species (RNS) are the best known molecules. This review article shows the current state of knowledge on the chemical specificity, relative rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 90 publications
0
43
0
2
Order By: Relevance
“…The sustained activation of GR during chronic stressful condition may decrease PVB expression by sensitizing interneuron activation and, possibly, through a toxic effect due to NO release. Indeed, NO may be converted in different reactive nitrogen species, thus leading to oxidative damage of proteins, lipids, and DNA that are able to alter neuronal homeostasis (Moniczewski et al, 2015). We also showed that prolonged stress exposure alters the NRF2-KEAP-antioxidant responsive element system, a master regulator of the antioxidative response (Sandberg et al, 2014), with a decrease of NRF2 expression that may impair the activation of antioxidant mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sustained activation of GR during chronic stressful condition may decrease PVB expression by sensitizing interneuron activation and, possibly, through a toxic effect due to NO release. Indeed, NO may be converted in different reactive nitrogen species, thus leading to oxidative damage of proteins, lipids, and DNA that are able to alter neuronal homeostasis (Moniczewski et al, 2015). We also showed that prolonged stress exposure alters the NRF2-KEAP-antioxidant responsive element system, a master regulator of the antioxidative response (Sandberg et al, 2014), with a decrease of NRF2 expression that may impair the activation of antioxidant mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…In the present work we used the chronic mild stress (CMS) model (Willner, 2017) to investigate the detrimental effects of stress on PVB+ cells in rat hippocampus and the potential contribution of a dysregulation in redox mechanisms, which have also been associated with the pathophysiology of several psychiatric disorders (Moniczewski et al, 2015; Smaga et al, 2015; Steullet et al, 2017). We have previously shown that CMS is able to induce depressive-like behaviors such as anhedonia (Rossetti et al, 2016) as well as cognitive impairment (Calabrese et al, 2017), which are associated with alterations in key molecular players for psychiatric disorders (Luoni et al, 2014; Calabrese et al, 2016b; Molteni et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The etiology of depression is multifactorial and related to disturbed monoaminergic transmission, changes in receptor function, dysregulation of the stress axis, a reduction of neurogenesis, activated inflammatory processes, or increased oxidative stress (Moniczewski et al 2015; Smaga et al 2015). Recent observations strongly support the involvement of the endocannabinoid (eCB) system in the pathogenesis of depression.…”
Section: Introductionmentioning
confidence: 99%
“…In the complete glucose oxidation process by cells are involved various metabolic pathways (glycolysis, Krebs cycle and the electron transport chain (ETC)) and some cellular compartments (cytoplasm, membrane and mitochondrial matrix). Under physiological conditions, the enzymes of the mitochondrial respiratory chain, as a result of metabolism, are responsible for a constant endogenous production of free radicals (such as reactive oxygen intermediates (ROI) and reactive nitrogen species (RNS)) [28]. The main source of ROS generation is the electron transport chain (ETC) in the mitochondria.…”
Section: Ros (Reactive Oxygen Species)mentioning
confidence: 99%